Podcasting for teachers : using a new technology to revolutionize teaching and learning - King, Kathleen P., 1958-; Gura, Mark (Emerging technologies for evolving learners., 2009)
This book introduces and explains this important new technology from the perspective of educators. It also provides new insights into the ways that technology can provide solutions to instructional needs that have not been sufficiently addressed until now. Not only does it provide concrete explanations, examples, models, and details about methods and resources that are not currently illustrated in other publications, but it also reveals a new rationale for the use of technology in education.This book helps readers apprehend critical issues essential to understanding and taking advantage of podcasting and related technologies as an educational resource:What podcasting isHow "to do" podcastingHow to plan podcasting-based activities for studentsHow to create podcasts as teaching resourcesHow to use podcasting for professional developmentModels developed specifically by the authors regarding:Podcast developmentEducators' learning curve in podcastingCost/benefit decision making regarding podcasting projectsK - 12 school district directors of curriculum and instruction and directors of professional development, as well as classroom teachers, principals, and instructional supervisors across the core curriculum and in the area of Instructional Technology; and teacher educators and other college faculty will find this book a valuable resource. Readers may use the book as part of their own efforts to expand their teaching or staff development practice. It can also be an important resource for Education courses in content instruction and Instructional Technology and serve as a valuable reference for educators interested in educational applications of technology.What you will find in this revised and updated edition?New for this edition are valuable additional insights and updates related to our additional years of experience in podcasting and new media. Critical updated URLs, screenshots, software comparisons, data, some fresh new curricular examples, and included references to our new series, The Teachers' Podcast and Transformation Education LIVE! We have also upgraded statistical information, advancements from the podcasting world, references, and biographical information. In short, the book is better than ever, in part because of suggestions form our many readers who are, teachers learners, and podcast listeners of course!